Suppression Benefits Boys in Taiwan: The Relation between Gender, Emotional Regulation Strategy, and Mental Health - Yeh, Kuang-Hui; Bedford, Olwen; Wu, Chih-wen; Wang, Shu-Yi; Yen, Nai-Shing (Frontiers in Psychology, 2017)
Emotion regulation (ER) strategies have a clear impact on mental health outcomes. In 2 studies (N = 695, N = 433) we investigated gender differences in the use of 2 ER strategies (reappraisal and suppression) to handle parent-child conflict in Taiwanese adolescents. We also identified the implications of these differences for some negative emotions (self-blame and resentment) and internalizing problems (psychosomatic symptoms and social withdrawal). Results of the correlation analyses in both studies indicated that reappraisal and suppression ER strategies are positively correlated only in male Taiwanese adolescents. Hierarchical regression analyses in the second study confirmed that reappraisal buffers male but not female adolescents against the negative effects of suppression on the arousal of negative affect and internalizing problems.